Fabrication of kW-level chirped and tilted fiber Bragg gratings and filtering of stimulated Raman scattering in high-power CW oscillators. (14th May 2019) - Jiao, Kerong; Shu, Jian; Shen, Hua; Guan, Zhiwen; Yang, Feiyan; Zhu, Rihong
Abstract : Suppression of stimulated Raman scattering (SRS) by means of chirped and tilted fiber Bragg gratings (CTFBGs) has become a key topic. However, research on high-power systems is still lacking due to two problems. Firstly, after the inscription, there are a large number of hydroxyl compounds and hydrogen molecules in CTFBGs that cause significant heating due to their strong infrared absorption. Secondly, CTFBGs can couple Stokes light from the core to the cladding and the coating, which causes serious heating in the coating of the CTFBG. Aimed at overcoming these bottlenecks, a process that combines constant-low-temperature and variable-high-temperature annealing is used to reduce the thermal slope of the CTFBG. Also, a segmented-corrosion cladding power stripping technology is used on the CTFBG to remove the Stokes light which is coupled to the cladding, which solves the problem of overheating in the coating of the CTFBG. Thereby, a CTFBG with both a kilowatt-level power-carrying load and the ability to suppress SRS in a fiber laser has been developed. Further, we establish a kW-level CW oscillator to test the CTFBG. Experimental results demonstrate that the power-carrying load of the CTFBG is close to 1 kW, the thermal slope is lower than $0.015\, ^{\circ }\text{C}/\text{W}$, and the SRS suppression ratio is nearly 23 dB.